Analisis Rasio Likuiditas dan Rasio Profitabilitas Pada PT. Bank Mandiri (persero) tbk Periode 2016-2019 - Nelly; Zein Ghozali; Masnoni; Sri Sutandi; Roy Saleh (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The purpose of research for writing this thesis is to find out the analysis of financial statements at PT. Bank Mandiri (Persero) Tbk in 2016-2019. Based on the description above, the author compiled this thesis with the title "Analysis of Liquidity Ratios, namely by using changes in the ratio of the Quick Ratio, and the Loan to Asset Ratio, while the Profitability Ratio Return on Assets, and Return on Equity in 2016-2019. This research is the entire financial report. The data used is taken from ICMD publications and the official website of the Indonesia Stock Exchange (IDX) www.idx.co.id. The data analysis method used is financial ratio analysis and descriptive analysis. The samples taken from this study are financial reports from 2016-2019. The sampling technique is aimed at taking subjects not based on strata, random or regions but based on a specific purpose. Based on the results of the study, it was concluded that in general the results of the analysis and previous discussion can be concluded that the development of the liquidity ratio and profitability ratio of PT. Bank Mandiri (Persero) Tbk in 2016-2017 with indicators Quick Ratio, Loan to Asset Ratio, Return on Assets, and Return on Equity shows a tendency to fluctuate and decline in financial conditions.